Framework for evaluating the risks of paralytic poliomyelitis after global interruption of wild poliovirus transmission - Aylward R. Bruce; Cochi Stephen L. (Bulletin of the World Health Organization, 2004)
With the interruption of wild poliovirus transmission globally, the need for new policies to deal with the post certification era will rapidly arise. New policies will be required in four areas: detection and notification of circulating polioviruses; biocontainment of wild, vaccine-derived and attenuated strains of poliovirus; vaccine stockpiles and response mechanisms; and routine immunization against polioviruses. A common understanding of the potential risks of paralytic poliomyelitis in the post-certification period is essential to the development of these policies. Since 2000, there has been increasing international consensus that the risks of paralytic poliomyelitis in the post-certification era fall into two categories: those due to the continued use of the oral poliovirus vaccine (OPV) and those due to future improper handling of wild polioviruses. The specific risks within both categories have now been defined, and an understanding of the frequency and potential burden of disease associated with each is rapidly improving. This knowledge and clarity have provided a framework that is already proving valuable for identifying research priorities and discussing potential policy options with national authorities. However, this framework must be regarded as a dynamic tool, requiring regular updating as additional information on these risks becomes available through further scientific research, programmatic work, and policy decisions.